2007
DOI: 10.1016/j.str.2007.02.007
|View full text |Cite
|
Sign up to set email alerts
|

ATP Ground- and Transition States of Bacterial Enhancer Binding AAA+ ATPases Support Complex Formation with Their Target Protein, σ54

Abstract: Transcription initiation by the sigma54 form of bacterial RNA polymerase requires hydrolysis of ATP by an enhancer binding protein (EBP). We present SAS-based solution structures of the ATPase domain of the EBP NtrC1 from Aquifex aeolicus in different nucleotide states. Structures of apo protein and that bound to AMPPNP or ADP-BeF(x) (ground-state mimics), ADP-AlF(x) (a transition-state mimic), or ADP (product) show substantial changes in the position of the GAFTGA loops that contact polymerase, particularly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(133 citation statements)
references
References 32 publications
(52 reference statements)
17
116
0
Order By: Relevance
“…As established earlier (Chen et al 2007), adding 1-5 mM ATP and ATP analogs to the assembled ring form of apo NtrC1 ATPase causes it to undergo large-scale conformational changes, but adding ADP does not. It was also shown that beginning near 1 mM concentration, ATP inhibits ATPase activity of the s54-dependent activators.…”
Section: Complexity Of Atp Binding To Ntrc1mentioning
confidence: 53%
See 2 more Smart Citations
“…As established earlier (Chen et al 2007), adding 1-5 mM ATP and ATP analogs to the assembled ring form of apo NtrC1 ATPase causes it to undergo large-scale conformational changes, but adding ADP does not. It was also shown that beginning near 1 mM concentration, ATP inhibits ATPase activity of the s54-dependent activators.…”
Section: Complexity Of Atp Binding To Ntrc1mentioning
confidence: 53%
“…Our prior biochemical and structural analyses suggested two things: (1) that apo and ADP-saturated rings form similar heptamer rings (SAXS data in Chen et al 2007) and (2) that strong clashes predicted for the interface between neighboring subunits that are alternately bound to ATP or ADP can be avoided by highly cooperative nucleotide binding and hydrolysis . In this study, we see that the symmetry in those ring structures is broken as binding of ATP analogs gradually drives the heptamers to form split-ring hexamers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, structural studies of several other hexameric ATPases have been interpreted as evidence that these enzymes cycle between states that are fully ATP-bound or ADP-bound. [23][24][25] Moreover, most HslU and HslUV crystal structures have six bound ATPs or ADPs (Fig. 1B), apparently supporting a symmetric or concerted mechanism of ATP hydrolysis.…”
Section: Introductionmentioning
confidence: 74%
“…Thus, the hydrolysis transition state configuration will exist when the DNA-binding hairpins reach the highest position of the cycle. This situation resembles the that of NtrC where the GAFTGA loops are directed towards the top of complex when bound to an ATP analog and occupy a higher position when bound to an ATP-transition state analog [84 ]. The loops are not projected upward when bound to ADP [84 ,85].…”
Section: Perturbations Of the Atpase Active Site Tethermentioning
confidence: 90%